Pengaruh Kualitas Produk dan Promosi terhadap Citra Merek Kopi Good Day di Kota Jambi - Mappadeceng, Riko; Tarmizi, Ahmad; Dewita, Lien Nancy (Universitas Batanghari Jambi, 2024)
The objectives of this research are as follows: 1) To determine and describe the product quality, promotion and brand image of Good Day Coffee in Jambi City. 2.) To determine the influence of product quality and promotion on the brand image of Good Day Coffee in Jambi City. The type of data required and collected in this research is quantitative data. The object of this research is Good Day Coffee customers in Jambi City. The data source in this research is Good Day Coffee customers in Jambi City who were taken through interviews by distributing questionnaires, the data and information obtained were analyzed descriptively, to analyze customer responses regarding brand image to purchasing decisions using a 5-choice scale. One brand of packaged instant coffee that is being intensively promoted using television media is the